"Efecto sobre caracteres cuantitativos en la evaluación de híbridos experimentales de maíz (Zea mays L.) en dos ambientes distintos". - Lucio Suárez, Walter Leonel (2015)
This research I conducted in the town of Windows on the grounds of Mr. Félix Rodríguez, located on the premises Cacheli Chico Canton windows in the Km 3 via Catarama and Vinces on the grounds of Agricultural Technology Institute Vinces, located in Vinces canton Km 1.5 via Vinces - Palestine Rivers Province. The property is located in the 79th geographical coordinates 47 west longitude and the 1st 32 minutes south latitude, with an altitude of 41 meters. The overall objective of this study was: To quantify the environmental, genetic effect on quantitative traits that determine the performance of maize hybrids and specific: To evaluate the agronomic performance of hybrid corn triples near windows and Vinces. Detect possible heterotic groups for grain yield between the lines evaluated and suggest the formation of potential heterotic patterns. Identify inbred lines suitable to intervene in the formation of hybrids with excellent performance...................................